1995
DOI: 10.1002/anie.199502821
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis Research in Berlin–Buch—Retrospective and Perspective Views

Abstract: “The following remarks consist partially of matter of fact, and partially of opinion. The former will be permanent; the latter must vary with the detection of error, or the improvement of knowledge. I hazard them with diffidence, and hope they will be examined with candour.” These declarations, which stem from the famous book “An Account of the Foxglove and some of its Medical Uses” by physician William Withering in 1785 in which he introduced preparations from digitalis leaves in the therapy of dropsy (cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…The involvement of cholinergic and histaminergic receptors could be excluded from the results of Ahmad et al (1995) who showed that the ability of verbascoside to reduce blood pressure in rats was unaffected by atropine (antimuscarinic agent) and chloro-pheniramine/cimetidine (antihistaminic agents). Inhibition of the Na -K -ATPase enzyme seemed unlikely since verbascoside appears to lack the structural requirements necessary to interact with this enzyme (Repke et al, 1995). Attempts to determine whether slow calcium channels were involved by using the clinical agent verapamil were inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of cholinergic and histaminergic receptors could be excluded from the results of Ahmad et al (1995) who showed that the ability of verbascoside to reduce blood pressure in rats was unaffected by atropine (antimuscarinic agent) and chloro-pheniramine/cimetidine (antihistaminic agents). Inhibition of the Na -K -ATPase enzyme seemed unlikely since verbascoside appears to lack the structural requirements necessary to interact with this enzyme (Repke et al, 1995). Attempts to determine whether slow calcium channels were involved by using the clinical agent verapamil were inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage of the C17 side chain begins with the treatment of (81) with hydroxylamine to afford the C20 oxime (82). Beckman rearrangement of (82) affords the ene-amide (83). Mild acid hydrolysis of (83) results in dehydroepiandrosterone acetate [853-23-6] (84) (133).…”
Section: Chemical Degradationmentioning
confidence: 99%
“…Duration of action can be determined in a similar way. The maximum rate of pressure rise dp/dtmax in this case is 266 mbar/40 ms = 6650 mbar/s [31] [14], [35], [36] The membrane-bound Na + -and K + -dependent adenosine triphosphatase (Na + , K + -ATPase) has been identified as the site of action of digitalis at the molecular level. Under physiological conditions this enzyme hydrolyzes adenosine triphosphate (ATP) to achieve the exchange of intracellular Na + for extracellular K + against concentration gradients.…”
Section: Pharmacological Investigationmentioning
confidence: 99%